Partes no signatarias del convenio arbitral: entre la realidad económica y la ficción juridica1 - García Larriva, Hugo (Iuris Dictio, 2013)
The following paper deals with the possibility of extending the application of an arbitration clause to nonsignatories. The main hypothesis is that, based on the doctrine of good faith, you can infer consent for arbitration from a person who has had an active and determinant participation in the negotiation, drafting, performance, and liquidation of or pretends to obtain benefits from a contract in which the arbitration clause is inserted. The paper concludes that an arbitration tribunal may apply a general standard to determine whether a non-signatory person can be considered as a party to a contract containing an arbitration agreement or not. This standard only applies if the lex arbitrios provisions do not require that the consent be given in a written form for the arbitration agreement's validity. In addition to it, two premises must converge: a) that the tribunal positively infers the non-signatory's consent by means of his active and determinant conduct; and, b) if the principle of Good Faith requires that the non-signatory be bound by the contract and the arbitration agreement.1